2019
DOI: 10.1126/sciadv.aav7848
|View full text |Cite
|
Sign up to set email alerts
|

Metals likely promoted protometabolism in early ocean alkaline hydrothermal systems

Abstract: One of the most plausible scenarios of the origin of life assumes the preceding prebiotic autotrophic metabolism in sulfide-rich hydrothermal vent environments. However, geochemical mechanisms to harness the reductive power provided by hydrothermal systems remain to be elucidated. Here, we show that, under a geoelectrochemical condition realizable in the early ocean hydrothermal systems, several metal sulfides (FeS, Ag2S, CuS, and PbS) undergo hour- to day-scale conversion to the corresponding metals at ≤−0.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 76 publications
(108 reference statements)
5
91
0
2
Order By: Relevance
“…Proposals for the nature of primordial CO2 fixation and energy conservation at biochemical origins typically posit the participation of external energy sources 50 such as UV light 51 , heat, impact, pressure, electrical currents, or ion gradients 28 to push organic synthesis forward. The reactions reported here require no additional energy source for a protometabolic acetyl-CoA pathway to unfold from H2 and CO2 other than the natural reactivity of two gasses and metal catalysts, indicating that neither membranes, though essential for the emergence of free-living cells 6,52-54 , nor external potentials 19,55 were required for primordial CO2 fixation along an exergonic, H2-dependent, nonenzymatic pathway to C3 products. The energy for the synthesis of compounds capable of phosphorylating ADP via substrate level phosphorylation 6,11,12 -for reactions reported here, and for those of the enzymatically catalysed acetyl-CoA pathwaystems from the exergonic synthesis of biologically relevant organic compounds from H2 and CO2.…”
Section: Resultsmentioning
confidence: 90%
“…Proposals for the nature of primordial CO2 fixation and energy conservation at biochemical origins typically posit the participation of external energy sources 50 such as UV light 51 , heat, impact, pressure, electrical currents, or ion gradients 28 to push organic synthesis forward. The reactions reported here require no additional energy source for a protometabolic acetyl-CoA pathway to unfold from H2 and CO2 other than the natural reactivity of two gasses and metal catalysts, indicating that neither membranes, though essential for the emergence of free-living cells 6,52-54 , nor external potentials 19,55 were required for primordial CO2 fixation along an exergonic, H2-dependent, nonenzymatic pathway to C3 products. The energy for the synthesis of compounds capable of phosphorylating ADP via substrate level phosphorylation 6,11,12 -for reactions reported here, and for those of the enzymatically catalysed acetyl-CoA pathwaystems from the exergonic synthesis of biologically relevant organic compounds from H2 and CO2.…”
Section: Resultsmentioning
confidence: 90%
“…We prepared metal sulfides including NiS by simply mixing an aqueous solution of the corresponding metal chloride and an aqueous solution of sodium sulfide. The obtained sulfides were exposed to a constant electric potential for 7 days in 100 mM NaCl at room temperature (25 ± Figure S8), [16] NiS showed no XRD signal for Ni 0 in the examined potential range (≤-1.0 VSHE) ( Figure 1a). The Ni 0 percentage up to 12% (Figure 1f) is well above the detection limit of XRD ( Figure S10) if the formation of meso-or macroscopic crystalline structure is assumed.…”
Section: Metal Sulfide Electroreductionmentioning
confidence: 99%
“…[15] It was later found that FeS undergoes day-scale electroreduction to Fe 0 . [16] The resultant FeS-Fe 0 assemblage, named FeS_PERM (FeS partially electroreduced to metal), showed exceptional capability of promoting various prebiotically important reactions owing to synergy between surface Fe sites with different oxidation states (Fe 2+ and Fe 0 ). [17,18] In our previous works, [15,16] NiS exhibited neither CO evolution nor Ni 0 formation detectable by X-ray diffraction (XRD) analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical gardens have been investigated in a variety of studies as a laboratory or experimental simulation for geological mineral structures such as hydrothermal vent chimneys (Figure 1). [1–7] Such geological structures exist in Earth's oceans and likely also formed on early Earth where they have been suggested as possible settings for the emergence of life [8,9] . Hydrothermal vents and chimneys have also been hypothesized to exist on other ocean worlds in our solar system such as Enceladus, a moon of Saturn [10,11] or Europa, a moon of Jupiter .…”
Section: Introductionmentioning
confidence: 99%